Jewish Theatre in Budapest: The question of belonging 1939-1944 - Anna Kalmár (Tropos, 2017)
The Hungarian government introduced a number of anti-Semitic laws that restricted Jewish ’presence’ between 1920 and 1944, first in universities, then in professional spheres and finally, in public places. By 1941 hardly any Jewish-born theatre workers were employed by the Budapest theatres. Simultaneously, the authorities gave permission for a Jewish theatrical initiative to launch, within the confines of the cultural organisation of the Pest Israelite congregation (OMIKE). The initiative, entitled ’Artists’ Action’ was seen as a kind of ‘cultural ghetto’ by the authorities, but to its member it represented a fight for continuous access to culture. It was also a cultural mission which provided a livelihood for 400 artists and unified thousands of people. Studying the Artists’ Action, its leaders, members and audience, also provides an insight into an identity in crisis: the search for a unified Hungarian Jewishness amidst social exclusion was actively supported by the practices of the cultural institution as well as the journal of the congregation. To read or download this article, please follow this link: http://discovery.ucl.ac.uk/1558834 DOI: 10.14324/111.2057-2212.067